Kinetics of Aqueous Cu(II) Biosorption onto Thevetia peruviana Leaf Powder - Medhi, Himani (ACS Omega, 2020)
[Image: see text] Copper is an essential micronutrient; however, as a result of its increasing demand, subsequent mining followed by its direct discharge into the environment has led to the contamination of our ecosystem. Thevetia peruviana (TP) is an ornamental herb of medicinal interest and is extensively used as an antipyretic and anticancer agent due to the presence of cardiac glycosides. In this work, we have explored the TP leaf powder as a biosorbent for Cu(II) removal from aqueous media and observed that it yields better results in comparison to other reported biosorbents for the removal of Cu(II). This work also emphasizes on the biosorption kinetics along with its plausible mechanism of interactions. The leaf powder characterized by FT-IR spectroscopy confirmed the diverse surface functionalities including hydroxyl, carbonyl, glycosides, etc. The morphology and elemental composition of the plant material have been investigated using SEM-EDAX analysis that confirms the heterogeneity and porosity of the biosorbent surface. The encouraging results revealed that the TP leaf powder could be used as a cost-effective biosorbent with an adsorption capacity of 187.51 mg g(–1) for Cu(II) in aqueous media at pH ∼ 5 and a temperature of 303 K. The complex functionality of the TP surface most likely played a significant role in attaining fast equilibrium within 60 min by following pseudo-second-order kinetics, having a rate constant of 2 × 10(3) mg g(–1) min(–1) that has been confirmed with statistical tools such as regression coefficient, chi-squared, and sum of error square tests. The adsorption mechanism is controlled by diffusion of Cu(II) from the liquid phase to the solid phase of the TP biosorbent followed by the chemical interaction between the biosorbent and the adsorbate with slow intraparticle diffusion on the biosorbent surface. The adsorption of Cu(II) on TP has been observed to rise from 59.29 to 197.63 mg g(–1) with the rise in the pH of the medium from 2 to 7. The adsorption of Cu(II) has been found to increase from 176.80 to 191.33 mg g(–1) with increasing temperature from 293–308 K, confirming the endothermic nature of the adsorption process. The thermodynamic study revealed the adsorption process to be spontaneous with negative ΔG (−10.43 to −13.74 kJ mol(–1)) and that it has an endothermic nature with positive ΔH (54.24 kJ mol(–1)). The isotherm study for Cu(II) on TP followed the Langmuir adsorption isotherm model with the maximum monolayer adsorption capacity of 303.03 mg g(–1) rather than Freundlich and Temkin isotherm models, which confirmed the chemical interaction between the sorbent and sorbate. FT-IR and SEM-EDAX analyses have also been used to confirm the adsorption of Cu(II) onto the TP surface. The present study revealed 99.7% Cu(II) desorption using 0.8 N HCl as the desorbent accompanied by a 69.71% regeneration efficiency of the TP biosorbent. After desorption of Cu(II), the regenerated TP could be disposed of in soil. The encouraging results revealed that TP could be used as an alternative and low-cost biosorbent for the removal of heavy metals from aqueous solutions.